PROBLEMATIKA IMPLEMENTASI PERATURAN DAERAH KABUPATEN KARO NOMOR 3 TAHUN 2012 TENTANG PAJAK DAERAH - Michail Wiliem's Siberonta; Manoras Taraja (Nommensen Journal of Legal Opinion, 2020)
Tax area is one of the important sources of local revenue to finance the development of a lauarge, real and responsible of aoutonoumos area, The role of the constructor visible in every project that undertaken by the government ic alwaayson the buzz of the project being build finance from the funds that have been mede lip of the society. Tax economic perspective as a mive from the private sector to the public sector. This understanding iustrates the exsistence of two situation being changed, first the ddiminished a bilitiy of individuals in control this understanding iustrates the sexsistence of two situation being changed. First the diminished abiling of individuals in control of resources for the importance of control goods and services. Increased local financial capasitiy in the provision of public goods and serulces the necessities of people’s live white the development from a legal perspektife is a bond that arises because of the regulations to the emergence of the comonity to defate certain income to the emergence of the comunitiy to defecate certain income to the region. The area that have the advantage to assert the impose and money of the area must be used to implement of the area, ftom this legal appreaceh to consider the law must be based on a regulation that ensures a legal. Certainty, both, both taxis as tax convectors and tax payers as payers tax payable. From various definitions give to the tax elther divectly or juridi cally drawn conclusion about the characteristics the exsistence of tunds transfer (resources) of the private sector (tax payers paying taxes) to the regional/state sector (tax administratios).